2022
DOI: 10.3390/ijms23147503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nutrition, Microbiota Transplant and Weight Loss Surgery on Dopaminergic Alterations in Parkinson’s Disease and Obesity

Abstract: Parkinson’s disease (PD), the second most common neurodegenerative disorder worldwide, is characterized by dopaminergic neuron degeneration and α-synuclein aggregation in the substantia nigra pars compacta of the midbrain. Emerging evidence has shown that dietary intake affects the microbial composition in the gut, which in turn contributes to, or protects against, the degeneration of dopaminergic neurons in affected regions of the brain. More specifically, the Mediterranean diet and Western diet, composed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 189 publications
0
27
0
Order By: Relevance
“…The Ruminococcus_torques_group has earlier been found enriched in children with ASD 42 , Irritable Bowel Syndrome 43 , Crohn’s disease 44 , and influenza-like illness 45 ; it was also found associated with the degradation of the intestinal mucosal layer 46 . Ruminococcus_torques species were further associated with a western diet (high energy, low nutrition) and neuroinflammation; it might also be related to reduction in striatal dopamine in Parkinson’s Disease (for a review, see 47 ). These studies suggest a role of Ruminococcus_torques_group in gut-barrier functioning and pro-inflammatory processes, which have previously been implicated in the etiology of psychiatric, neurodevelopmental, and neurological disorders 48, 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The Ruminococcus_torques_group has earlier been found enriched in children with ASD 42 , Irritable Bowel Syndrome 43 , Crohn’s disease 44 , and influenza-like illness 45 ; it was also found associated with the degradation of the intestinal mucosal layer 46 . Ruminococcus_torques species were further associated with a western diet (high energy, low nutrition) and neuroinflammation; it might also be related to reduction in striatal dopamine in Parkinson’s Disease (for a review, see 47 ). These studies suggest a role of Ruminococcus_torques_group in gut-barrier functioning and pro-inflammatory processes, which have previously been implicated in the etiology of psychiatric, neurodevelopmental, and neurological disorders 48, 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean Diet (MD) consists of plant-based ingredients including wheats, cereals, nuts, fruits, vegetable, omega-3 polyunsaturated fatty acids, with high amounts of fibers and polyphenols [ 8 ]. Collectively, these ingredients have been shown to have beneficial effects on lipid imbalances through their antioxidant and anti-inflammatory effects [ 115 , 116 ] as shown via reduction in TNF-alpha and LPS concentrations [ 117 , 118 ].…”
Section: Diet and Its Effects On Gut Microbiota And Dyslipidemiamentioning
confidence: 99%
“…Other less abundant gut bacteria species belong to the phyla Actinobacteria , Proteobacteria , and Verrucomicrobia [ 3 ]. In a healthy gut, homeostatic microbial composition is achieved via cross talk between host and microbiota through a commensal relationship [ 4 ], though negative changes in gut microbial composition and diversity can contribute to the development of disease states [ 5 , 6 , 7 , 8 , 9 ]. Overall, gut microbiota serve a variety of host functions including regulation of metabolism and immune system as well as maintaining gut mucosal barrier integrity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a recent case series of six patients with PD who underwent FMT via colonoscopy, it was shown that both motor and non-motor symptom improved in five patients ( 89 ). Thus, optimizing gut microbial composition in PD helps to improve dopamine signaling throughout the body, therefore FMT may exert its benefits via these pathways ( 11 , 15 ).…”
Section: Fecal Microbiota Transplant In Neuropsychiatric Disordersmentioning
confidence: 99%
“…Two main bacterial phyla, Firmicutes and Bacteroidetes, predominate the human gut, accounting for 90% of the species that reside there ( 13 ). As such, the Firmicutes/Bacteroidetes ratio, has been often used as a marker to identify correlations with the onset of diseases such as obesity, type 2 diabetes mellitus (T2DM), inflammatory bowel disease and colorectal cancer ( 14 , 15 ). Imbalances in the intestinal microbiota, also called dysbiosis, play a key role in changes in the Firmicutes/Bacteroidetes ratio, with decreasing microbial diversity, contributing to disease onset.…”
Section: Introductionmentioning
confidence: 99%